Fluxes of CH4, CO2, NO, and N2O in an improved fallow agroforestry system in Eastern Amazonia - Verchot, Louis V.; Brienza, S.; Oliviera, V.C. de; Mutegi, J.K.; Cattanio, J.H.; Davidson, E.A. (Elsevier, 2008)
The objective of this study was to evaluate the effect of leguminous fallows on ethane (CH4), carbon dioxide (CO2), N oxides (N2O and NO) fluxes.We measured CH4, N2O, NO, and CO2 fluxes from improved fallows of Inga edulis and Acacia mangium during two successive fallow periods in an old agricultural frontier on sandy soils in eastern Amazonia. Sampling for the first fallow period was done in 1996 and 1997 while that for the second fallow was done in 1999 and 2000. We observed net CH4 uptake during majority of the sampling campaigns.We did not observe any significant difference in CH4 flux between improved fallows and unimproved fallows (control) during either of the sampling periods (P > 0.05).We observed significantly higher uptake during the dry season relative to wet season, indicating the importance of soil water content and gas transport on CH4 fluxes. For both wet and dry seasons, soil respiration rates (CO2), N2O and NO fluxes were similar for improved fallow plots and the control (P > 0.05). We did not observe any significant seasonality in soil respiration or NO fluxes, but there was a significant difference in N2O flux between seasons (P = 0.0638). Contrary to other studies, our observations suggest that improved fallows using N-fixing trees do not appear to decrease the soil CH4 sink and also do not seem to increase CO2 and N-oxide emission in these sandy Amazonian soils. The result for N oxides is particularly pertinent to greenhouse gas (GHG) accounting methods that assess N2O emissions as a fraction of N fixation